2014
DOI: 10.1371/journal.pone.0095110
|View full text |Cite|
|
Sign up to set email alerts
|

Distinct Cell Clusters Touching Islet Cells Induce Islet Cell Replication in Association with Over-Expression of Regenerating Gene (REG) Protein in Fulminant Type 1 Diabetes

Abstract: BackgroundPancreatic islet endocrine cell-supporting architectures, including islet encapsulating basement membranes (BMs), extracellular matrix (ECM), and possible cell clusters, are unclear.ProceduresThe architectures around islet cell clusters, including BMs, ECM, and pancreatic acinar-like cell clusters, were studied in the non-diabetic state and in the inflamed milieu of fulminant type 1 diabetes in humans.ResultImmunohistochemical and electron microscopy analyses demonstrated that human islet cell cluste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 36 publications
(47 reference statements)
1
18
0
Order By: Relevance
“…et al(32) with some modifications. Briefly, pieces of mouse pancreata were cut and immediately placed into McDowell Trump's fixative (Cat# 18030-10; Electron Microscopy Sciences) for 1h.…”
mentioning
confidence: 99%
“…et al(32) with some modifications. Briefly, pieces of mouse pancreata were cut and immediately placed into McDowell Trump's fixative (Cat# 18030-10; Electron Microscopy Sciences) for 1h.…”
mentioning
confidence: 99%
“…In diffuse Langerhans islets, we found that some endocrine cells appear to Correlative Light-Electron Microscopy (CLEM) and 3D Volume Imaging of Serial Block-Face… DOI: http://dx.doi.org /10.5772/intechopen.81716 have direct cell-to-cell contacts with adjacent endocrine and exocrine acinar-like cells (Figure 7). These results indicate that electric or metabolic coupling exists not only between adjacent endocrine cells but also between endocrine cells and the surrounding pancreatic exocrine acinar-like cell clusters [10,44]. We also identified insulin and REG1α double-positive cells that contained zymogen-like condensing granules in the endocrine islet cells, with several types of granules morphologically classified as β-, δ-, and PP-cell like granules (Figure 6).…”
Section: Diffuse Type Of Langerhans Isletmentioning
confidence: 66%
“…Other islets are "diffuse"; they have no nests separating them from adjacent exocrine acini. However, the ultrastructure supporting "diffuse" pancreatic islets including islet-encapsulating basement membranes, extracellular matrix, and adjacent exocrine acini have not been elucidated in detail [5,[10][11][12][13]. Regenerating islet-derived gene 1 alpha (REG1α) is secreted by the exocrine pancreas or β cells and affects islet cell regeneration [14,15], thereby regulating the development of Langerhans islet architecture and diabetogenesis [10,16,17].…”
Section: Langerhans Islets Have Compact and Diffuse Type Isletsmentioning
confidence: 99%
“…The findings showed that the acinar‐like cell clusters touching islet endocrine cells are distinct because the cell clusters are packed with pancreatic islet clusters and surrounded by common basement membranes/extra cellular matrix. Furthermore, the acinar‐like cell clusters express regenerating gene protein Iα and secrete directly into neighbouring islet endocrine cells in the nondiabetic state, and the cell clusters overexpress regenerating gene protein Iα in the inflamed milieu of fT1D with marked self‐replication of islet cells …”
Section: Pathologymentioning
confidence: 99%